2015
DOI: 10.1007/s11207-015-0789-6
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Reconnection Rates and Energy Release in a Confined X-class Flare

Abstract: We study the energy-release process in the confined X1.6 flare that occurred on 22 October 2014 in AR 12192. Magnetic-reconnection rates and reconnection fluxes are derived from three different data sets: space-based data from the Atmospheric Imaging Assembly (AIA) 1600Å filter onboard the Solar Dynamics Observatory (SDO) and ground-based Hα and Ca ii K filtergrams from Kanzelhöhe Observatory. The magnetic-reconnection rates determined from the three data sets all closely resemble the temporal profile of the h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 51 publications
(75 reference statements)
5
23
1
Order By: Relevance
“…We also speculate that due to the Neupert effect (Neupert 1968;Veronig et al 2002), the derived correlation between the reconnection flux and the peak soft X-ray flux will lead to a strong correlation between the peak reconnection flux rate and the peak hard X-ray flux, in agreement with earlier studies of individual events (e.g. Qiu et al 2002;Veronig & Polanec 2015).…”
Section: Discussionsupporting
confidence: 90%
“…We also speculate that due to the Neupert effect (Neupert 1968;Veronig et al 2002), the derived correlation between the reconnection flux and the peak soft X-ray flux will lead to a strong correlation between the peak reconnection flux rate and the peak hard X-ray flux, in agreement with earlier studies of individual events (e.g. Qiu et al 2002;Veronig & Polanec 2015).…”
Section: Discussionsupporting
confidence: 90%
“…Previously, , Thalmann et al (2015), and Veronig & Polanec (2015) also investigated this well observed flare using SDO, RHESSI and IRIS. Thalmann et al (2015) and Veronig & Polanec (2015) mainly focused on the magnetic reconnection rates and the RHESSI HXR profiles of this flare, and investigated the relationship between Doppler velocity patterns derived from IRIS Fe XXI and C I and the RHESSI HXR intensity. Those studies showed that the flare energy is injected into high energy electrons, and that they could driver the evaporation flow in the flare.…”
Section: Introductionmentioning
confidence: 98%
“…It is fair to mention that this AR is rather unusual as being extremely large but, interestingly, CME-poor. AR 12192 has been described well in the literature (Veronig & Polanec, 2015;Jiang et al, 2016;Liu et al, 2016). Here, again, we notice the fol-lowing remarkable properties of the W G M and the distance.…”
Section: Discussionmentioning
confidence: 78%